Reduced miR-146a Promotes REG3A Expression and Macrophage Migration in Polymyositis and Dermatomyositis - Jiang, Tingwang; Huang, Yuanlan; Liu, Haohao; Xu, Qiangwei; Gong, Yanping; Chen, Yao; Hu, Xiaowei; Han, Zhijun; Gao, Mingzhu (Frontiers in Immunology, 2020)
Background: Growing evidence from studies elsewhere have illustrated that microRNAs (miRNAs) play important roles in Polymyositis and Dermatomyositis (PM/DM). However, little has been reported on their relationship with regenerating islet-derived protein 3-alpha (REG3A) as well as their associative roles in macrophage migration. Therefore, this study sought to establish the association between miR-146a and REG3A as well as investigate their functional roles in macrophage migration and PM/DM pathogenesis. Methods: Peripheral blood mononuclear cells (PBMCs) were isolated from PM/DM patients and healthy controls through density centrifugation. Macrophages were obtained from monocytes purified from PBMCs via differentiation prior to their transfection with microRNA (miRNA) or plasmids to investigate cell migration with transwell assay. An experimental autoimmune myositis (EAM) murine model was used to investigate PM/DM. Real-time PCR and western blot analysis were conducted to determine the expression levels of miR-146a, IFN-γ, IL-17A and REG3A. Results: The mRNA expression level of miR-146a markedly decreased while the mRNA level of REG3A, IFN-γ and IL-17A expression increased substantially in PBMCs from PM/DM patients compared with the healthy controls. The levels of IFN-γ and IL-17A in serum from PM/DM patients was much higher than the healthy controls. Immunohitochemistry analysis showed that REG3A expression increased in muscle tissues from patients. Consistent with clinical data, the mRNA expression level of miR-146a also decreased whereas the mRNA and protein level of REG3A, IFN-γ and IL-17A significantly increased in the muscle tissues of EAM mice. Moreover, miR-146a inhibited monocyte-derived macrophage migration and REG3A promoted macrophage migration. In addition, IL-17A induced REG3A expression, while miR146a inhibited expression of REG3A in monocyte-derived macrophages from the PBMCs of the healthy donors. Notably, inhibition of macrophage migration by miR-146a was via the reduction of REG3A expression. Conclusions: Reduced miR-146a expression in PM/DM leads to increased REG3A expression that increases inflammatory macrophage migration, which may be a possible underlying mechanism of DM/PM pathogenesis.